2013
DOI: 10.1515/jpem-2012-0154
|View full text |Cite
|
Sign up to set email alerts
|

Early occurrence of cerebral white matter abnormality detected in a neonate with salt-wasting congenital adrenal hyperplasia

Abstract: The development of white matter signal abnormalities on magnetic resonance brain imaging (MRI) in children and young adults with congenital adrenal hyperplasia has been well documented. Existing theories regarding the development of these findings include effects of electrolyte imbalances, effects of disease-related hormone abnormalities, and non-physiologic long-term administration of corticosteroids. Many of the patients previously described were normal neurologically. We describe the case of white matter si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Of note, several studies based on MRI have described brain white matter abnormalities in children with CAH, with the radiological changes that can be sometimes detected from the first days of life in children with classic CAH [49, 55]. In addition to the white matter changes, moderate atrophy in the right temporal cortex, small volume hippocampus, and agenesis or thinning of the corpus callosum were observed in the long term follow-up of children with classic CAH [5658].…”
Section: Adrenal Insufficiency and The Paediatric Brainmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, several studies based on MRI have described brain white matter abnormalities in children with CAH, with the radiological changes that can be sometimes detected from the first days of life in children with classic CAH [49, 55]. In addition to the white matter changes, moderate atrophy in the right temporal cortex, small volume hippocampus, and agenesis or thinning of the corpus callosum were observed in the long term follow-up of children with classic CAH [5658].…”
Section: Adrenal Insufficiency and The Paediatric Brainmentioning
confidence: 99%
“…In addition, hyponatremia, potentially leading to myelinolysis, has been suggested as a potential contributing factor to the impaired myelin formation in these patients [55, 56]. Some authors have also suggested that hormonal imbalance related to a deficiency in cortisol and aldosterone and an overproduction of 17-OH-progesterone and androgen may further cause a destabilisation of the myelin molecule leading to its degeneration [56].…”
Section: Adrenal Insufficiency and The Paediatric Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the brain MRI findings in newborn infants with CAH have not been clarified except in one case report (8). …”
Section: Introductionmentioning
confidence: 99%